First-line immune checkpoint inhibitors in low programmed death-ligand 1-expressing population - Zhang, Feiyang; Chen, Guoming; Yin, Yixin; Chen, Xiaojiang; Nie, Runcong; Chen, Yingbo (Frontiers in Pharmacology, 2024)
Inhibitors of programmed cell death 1 (PD1) and its ligand (PDL1) have exhibited favorable long-term survival in many types of advanced-stage cancer and current approvals have to date been granted in certain tumour types irrespective of PD-L1 status. Here, a total of 34 trials were included to extract individual patient data (IPD) to evaluate the survival benefit of first line PD1/PDL1 inhibitors vs. standard-of-care (SOC) in patients with PDL1 < 1%. In term of anti-PD-1/PD-L1 monotherapy, OS (HR=0.90, 0.81-1.01) and PFS (HR=1.11, 0.97-1.27) between PD-1/PD-L1 inhibitor group and SOC group were comparable. In term of anti-PD-1/PD-L1 combination therapy, PD-1/PD-L1 inhibitor group exhibited longer OS (median 19.5 months vs.16.3 months; HR=0.83, 0.79-0.88, P<0.001) and PFS than those of SOC group (median 8.11 months vs.6.96 months; HR=0.82, 0.77-0.87, P<0.001). Subgroup analysis showed that survival benefit was mainly observed in non-small cell lung cancer (NSCLC) (HROS=0.74; HRPFS=0.69; P<0.001), small-cell lung cancer (SCLC) (HROS=0.58, P<0.001; HRPFS=0.55, P=0.030), esophageal squamous cell carcinoma (ESCC) (HROS=0.62, P=0.005; HRPFS=0.79, P<0.001), melanoma (HROS=0.53, P<0.001) and nasopharyngeal carcinoma (NPC) (HRPFS=0.35, P=0.013). In conclusion, Anti-PD-1/PD-L1 combinational therapy rather than monotherapy exhibit survival benefit in the low PD-L1 population in the first-line setting, and the survival benefit was mainly observed in specific tumor types.